Individuals with chronic low back pain have greater difficulty in engaging in positive lifestyle behaviours than those without back pain: An assessment of health literacy - Briggs, Andrew; Jordan, J.; O'Sullivan, Peter; Buchbinder, R.; Burnett, A.; Osborne, R.; Straker, Leon (Biomed Central Ltd, 2011)
Background: Despite the large volume of research dedicated to understanding chronic low back pain (CLBP), patient outcomes remain modest while healthcare costs continue to rise, creating a major public health burden. Health literacy - the ability to seek, understand and utilise health information - has been identified as an important factor in the course of other chronic conditions and may be important in the aetiology of CLBP. Many of the currently available health literacy measurement tools are limited since they measure narrow aspects of health literacy. The Health Literacy Measurement Scale (HeLMS) was developed recently to measure broader elements of health literacy. The aim of this study was to measure broad elements of health literacy among individuals with CLBP and without LBP using the HeLMS. Methods: Thirty-six community-dwelling adults with CLBP and 44 with no history of LBP responded to the HeLMS. Individuals were recruited as part of a larger community-based spinal health study in Western Australia. Scores for the eight domains of the HeLMS as well as individual item responses were compared between the groups.Results: HeLMS scores were similar between individuals with and without CLBP for seven of the eight health literacy domains (p > 0.05). However, compared to individuals with no history of LBP, those with CLBP had a significantly lower score in the domain 'Patient attitudes towards their health' (mean difference [95% CI]: 0.46 [0.11-0.82]) and significantly lower scores for each of the individual items within this domain (p < 0.05). Moderate effect sizes ranged from d = 0.47-0.65. Conclusions: Although no differences were identified in HeLMS scores between the groups for seven of the health literacy domains, adults with CLBP reported greater difficulty in engaging in general positive health behaviours. This aspect of health literacy suggests that self-management support initiatives may benefit individuals with CLBP.